Incidence and pathological features of IgA nephropathy before and during the COVID-19 pandemic - Wen Liu; Ricong Xu; Di Wu; Zhihang Su; Yuan Cheng; Haofei Hu; Xinzhou Zhang; Qijun Wan (Scientific Reports)
Abstract IgA nephropathy (IgAN) imposes a substantial burden of illness and death. However, a systematic evaluation of the impact of the COVID-19 pandemic on the incidence and pathology of IgAN has yet to be performed. In this study, we analyzed kidney biopsy results from two medical institutions, covering the timeframe from January 2016 to May 2023. We conducted statistical analyses on various glomerular diseases according to their corresponding pathological diagnoses. Our objective was to compare the incidence of different glomerular diseases before and during the COVID-19 pandemic. The study focused on variations in the incidence of IgAN, and collected clinical and pathological data to assess pathological changes using the Oxford Classification (MEST-C). The findings revealed a significant increase in the incidence of IgAN during the COVID-19 pandemic, from 39.9% prior to the pandemic to 46.3% during it, representing a net increase of 6.4% (P < 0.001). Although clinical manifestations and laboratory indicators of disease activity in IgAN patients remained consistent over both periods, observable changes occurred in pathological features. Specifically, the proportions of M1 and E1 lesions according to the Oxford classification significantly increased during the pandemic, with odds ratios of 11.764 (95% CI 5.583–24.789, P < 0.001) and 1.718 (95% CI 1.114–2.649, P = 0.014), respectively. Our results indicate that the incidence of IgAN has risen during the COVID-19 pandemic, along with exacerbated renal damage and elevated proportions of M1 and E1 in the Oxford classification.